Frontières, défis environnementaux et enjeux de gouvernance dans des bassins fluviaux au cœur de dynamiques territoriales complexes - Joan Tort Donada; Alexis Sancho Reinoso; Teresa Navas Ferrer (Belgeo)
The article undertakes an in-depth study of the territorial problems currently faced by the Noguera Ribagorçana, a highly representative river ecosystem in the central sector of the southern slopes of the Pyrenees. This river, because of the physical characteristics of its basin, highly fragmented, and the magnitude of the hydroelectric power project implemented there in the middle of the 20th century, has become a paradigmatic example of the complexity of the interaction between river systems and human communities, and of the conflicts over water uses associated with such that interaction. In this context, the article seeks to analyze three fundamental questions: the conditioning role played over time, but also currently, by the border factor ; the implications of the intensive hydroelectric exploitation of the river as a major environmental challenge, and, finally, the governance and integral management of the Noguera Ribagorçana valley as the most prominent territorial challenge.